The Method of Elimination of Vibrations and Forces Excited by Unbalanced Rotary Machines with Inaccesible Rotor - J. Michalczyk; G. Cieplok (Engineering Transactions)
Possibilities of application of the method of synchronous elimination to the reduction of vibrations and forces in unbalanced rotary machines with inaccessible axes were considered in this paper. The conditions were formulated, which have to be satisfied by the system of inertia vibrators to achieve a stable solution of zero motion of the system in a stationary state. Theoretical considerations have been supported by numerical simulation of motion of the system: rotary machine - off-axial synchronous eliminator, and by experiments. The algorithm of optimization of the real system has been proposed.